Case report: Seropositive myasthenia gravis complicated by limbic encephalitis positive for antibodies to AMPAR and Lgi1 - Nes, Magne Solberg; Haugen, Mette; Haugland, Hans Kristian; Gilhus, Nils Erik; Vedeler, Christian Alexander (Frontiers in Neurology, 2023)
Objectives Autoantibodies to the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) and leucine-rich glioma-inactivated 1 (Lgi1) are associated with autoimmune encephalitis. We describe an acetylcholine receptor (AChR) positive patient with myasthenia gravis who developed limbic encephalitis with antibodies to AMPAR and Lgi1 Methods A single case report with detailed, prospective clinical and biomarker data including serial laboratory testing and histopathology. Results A 49-year-old female was diagnosed with anti-AChR antibody positive generalized myasthenia gravis in 1983. Nine months after the removal of a thymoma in 1984, she developed influenza-like symptoms and then symptoms of limbic encephalitis. Retrospective analysis of serum showed high concentrations of anti-AMPAR and lower concentrations of anti-Lgi1 antibodies. Cerebral CT was normal, EEG showed bifrontal dysrhythmia and CSF mild pleocytosis. Immuno-histochemical examination of the thymoma confirmed staining for Glur2, a subunit of AMPAR. The patient recovered with mild sequelae, but low levels of anti-AMPAR and anti-Lgi1 antibodies were detectable for over 25 years subsequently. Discussion This case confirms earlier reports of AMPAR-associated autoimmune encephalitis co-occurring with thymoma and myasthenia gravis and is unique in its observational length. It shows, moreover, that antibodies to AMPAR and Lgi1 can persist despite clinical recovery.